PELAKSANAAN PERJANJIAN KERJASAMA PENYALURAN LPG 3 KG ANTARA AGEN PT. SARI BUMI RAYA DENGAN PANGKALAN D’HUTAWEST - Putri Rahmadani; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The implementation of the cooperation agreement is the process and method of carrying outthe agreement or agreement of the parties to do something that gives rise to a relationship of rights andobligations of the parties in achieving common goals. Channeling comes from the word channel, whichmeans flowing, forwarding. Liquefied Petroleum Gas, hereinafter referred to as LPG, is a liquefiedhydrocarbon gas under pressure to facilitate storage, transportation and handling, which basicallyconsists of propane, butane or a mixture of both. The purpose of this thesis writer, first is to find out theimplementation of the cooperation agreement for the distribution of 3 kg LPG between agents of PT. SariBumi Raya with D'Hutawest base. Second, to find out the settlement of disputes in the cooperationagreement for the distribution of 3 kg LPG between agents of PT. Sari Bumi Raya with D'Hutawest base.This type of research is sociological legal research or is called empirical legal research.Sociological legal research is legal research that is intended to study and analyze the operation of law insociety, which is manifested in the legal behavior of society. This research was conducted at theD'Hutawest base which is located in the Sukamulia Village, Sail District, Pekanbaru City, Riau. Thesample and population in this study are representatives of PT. Sari Bumi Raya employees andD’Hutawest base owners. Sources of data obtained based on primary and secondary data, data collectiontechniques in research using interviews and literature review.The result of this research, there are two things that can be concluded, the first is theimplementation of the cooperation agreement for the distribution of 3 kg LPG between the agents of PT.Sari Bumi Raya with the D'Hutawest base was not fulfilled. The D'Hutawest Base is said to be included ina default where the debtor fulfills the performance, but not as it should. Second, the settlement of disputesin the cooperation agreement for the distribution of 3 kg LPG between agents of PT. Sari Bumi Raya withthe D'Hutawest base, namely by using an out-of-court settlement is negotiation. The author's suggestion,to the agents of PT. Sari Bumi Raya is expected to be more able to provide direction or socialize aboutthe distribution of 3 Kg LPG like what is good and right to the D'Hutawest base even though there arerules that are not listed in the cooperation agreement.Keywords: Implementation, cooperation agreements, agent, base